2007
DOI: 10.1038/sj.jp.7211633
|View full text |Cite
|
Sign up to set email alerts
|

Serious community-acquired neonatal infections in rural Southeast Asia (Bohol Island, Philippines)

Abstract: Objective: To determine the bacterial etiology, clinical presentation and risk factors for outcome of serious community-acquired infections in young infants.Study Design: Infants younger than 60 days, admitted for severe pneumonia or suspected sepsis/meningitis were prospectively evaluated using complete blood count, blood culture, chest radiograph, cerebrospinal fluid (CSF) culture in suspected meningitis. w 2 or Fisher's exact test and stepwise logistic regression were used for analysis.Results: Thirty-four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Furthermore, on the basis of either maternal report or the serum antimicrobial substance test, ~14% of neonates with cultures received antibiotics before specimen sampling, potentially further impairing sensitivity. Overall, the positivity rate of 5.8% (95% CI, 3.9%–8.2%) was comparable to those in studies of community-acquired neonatal infection in Bohol, the Philippines (4.4% [95% CI, 3.1%–6.2%]), and in Matlab, Bangladesh (13.8% [6.0%–27.2%]) [6, 8]. These low positivity rates may reflect a lack of specificity in clinical criteria, suggesting the need to further refine IMCI algorithms [5], in addition to the limitations of conventional blood cultures.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Furthermore, on the basis of either maternal report or the serum antimicrobial substance test, ~14% of neonates with cultures received antibiotics before specimen sampling, potentially further impairing sensitivity. Overall, the positivity rate of 5.8% (95% CI, 3.9%–8.2%) was comparable to those in studies of community-acquired neonatal infection in Bohol, the Philippines (4.4% [95% CI, 3.1%–6.2%]), and in Matlab, Bangladesh (13.8% [6.0%–27.2%]) [6, 8]. These low positivity rates may reflect a lack of specificity in clinical criteria, suggesting the need to further refine IMCI algorithms [5], in addition to the limitations of conventional blood cultures.…”
Section: Discussionsupporting
confidence: 58%
“…S. aureus was also the most prevalent among neonates in the population-based Matlab ALRI study (5/8) [8] and in the facility-based 4-country WHO Young Infants Clinical Signs Study (19/84) [4]. However, the etiology in our study population is markedly different from bacterial profiles of nosocomial neonatal infections in Bangladesh [34] and of nonnosocomial infections among young infants <60 days old in rural Philippines [6], where gram-negative pathogens such as Klebsiella pneumonia , Pseudomonas aeruginosa , and Enterobacter species predominate. Group B streptococci were uncommonly isolated, similar to hospital-based studies from Bangladesh [20] and other locations in developing countries [35, 36].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this study, we found that gram negatives were most prevalent, of which the most common were E. coli , K. pneumonia and H. influenzae , while in blood cultures, the most common pathogen was K. pneumoniae . These findings are similar to data in Malaysia showing that E. coli and K. pneumoniae are also common causes of CAP but different from the findings in the United States 14,15 . These different findings may be due to the differences in geographical exposure and prevalence of bacteria.…”
Section: Discussionsupporting
confidence: 75%
“…This study showed that compared to sepsis and meningitis, radiographic pneumonia was mild and uncommon, present in only 10% of infants with an 8.8% case fatality rate (CFR). However, in a large study that we conducted on serious community acquired infections among infants below 2 months of age (Quiambao et al. 2007), we noted that radiographic pneumonia was present in 27%, with 21% CFR.…”
Section: Introductionmentioning
confidence: 92%